Tryptophan catabolism in cancer: beyond IDO and tryptophan depletion - Platten, Michael; Wick, Wolfgang; Eynde, Benoit van den (Cancer research, 2012)
Tryptophan catabolism in cancer is increasingly being recognized as an important microenvironmental factor that suppresses antitumor immune responses. It has been proposed that the essential amino acid tryptophan is catabolized in the tumor tissue by the rate-limiting enzyme indoleamine-2,3-dioxygenase (IDO) expressed in tumor cells or antigen-presenting cells. This metabolic pathway creates an immunosuppressive milieu in tumors and in tumor-draining lymph nodes by inducing T-cell anergy and apoptosis through depletion of tryptophan and accumulation of immunosuppressive tryptophan catabolites. Competitive inhibitors of IDO are currently being tested in clinical trials in patients with solid cancer, with the aim of enhancing the efﬁcacy of conventional chemotherapy. There are, however, certain tumor types that are capable of catabolizing tryptophan but are largely IDO-negative. Recent evidence from studies in malignant gliomas and other types of cancers points to alternative enzymatic pathways of tryptophan catabolism involving tryptophan-2,3-dioxygenase (TDO). TDO, which is considered responsible for regulating systemic tryptophan levels in the liver, is constitutively expressed in some cancers and is equally capable of suppressing antitumor immune responses. Depletion of tryptophan induces signaling events in T cells, leading to anergy and apoptosis; however, active immunomodulation by accumulating tryptophan catabolites, most notably kynurenine, appears to play an equally important role. These immunomodulatory effects of kynurenine are mediated by the aryl hydrocarbon receptor. This intracellular transcription factor has classically been viewed as a receptor for environmental toxins, such as dioxin, and its important role in inﬂuencing immune responses, especially in epithelial barriers, is only beginning to emerge. This review summarizes the exciting developments in our understanding of tryptophan catabolism as a key factor in the immunobiology of cancer. Cancer Res; 72(21); 5435-40. Ó2012 AACR.